(e/5)-4=-3

Simple and best practice solution for (e/5)-4=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (e/5)-4=-3 equation:



(e/5)-4=-3
We move all terms to the left:
(e/5)-4-(-3)=0
We add all the numbers together, and all the variables
(+e/5)-4-(-3)=0
We add all the numbers together, and all the variables
(+e/5)-1=0
We get rid of parentheses
e/5-1=0
We multiply all the terms by the denominator
e-1*5=0
We add all the numbers together, and all the variables
e-5=0
We move all terms containing e to the left, all other terms to the right
e=5

See similar equations:

| 2(x-3)^2-10=22 | | n/2-1/3=1/6 | | 2a+3=3a-1 | | 6x + 4 = 9x + 22 | | 7a(-7a)=0 | | a/3+2=13 | | 7m+4=73 | | 3×(2+3)=x | | x+31+x+20+x=180 | | 10x+3=12x-17 | | 73/4-x=11/2 | | x-0.15=1/4 | | 120+120+120+110+x+(x+10)=720 | | 6n+4=4 | | 82+2x=94+x | | (5x-2)^2/x-3=4-20x+25x^2/24-11x+x^2 | | 6m^2-m-22=0 | | 3y+5=44=13 | | H=3+14t-5t2 | | 9×3^3x+4=9^x | | 3a+2=a-7 | | (-3/2)^12=(-9/16)-2x | | 7+8x=52x+31 | | 7+8x=52+31 | | 2/9=10/p-4 | | 8/5=3/x-8 | | 3(x+)=24 | | 1/3-x-2=3/5 | | m-1/5=4 | | n-10/8=9/3 | | (-9/16)^-2x=(-3/2)^12 | | x/x+3=3/5 |

Equations solver categories